2019
DOI: 10.1038/s41467-019-11996-y
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for grain boundary passivation in Cu(In,Ga)Se2 solar cells through alkali-fluoride post-deposition treatments

Abstract: The properties and performance of polycrystalline materials depend critically on the properties of their grain boundaries. Polycrystalline photovoltaic materials – e.g. hybrid halide perovskites, copper indium gallium diselenide (CIGSe) and cadmium telluride – have already demonstrated high efficiencies and promise cost-effective electricity supply. For CIGSe-based solar cells, an efficiency above 23% has recently been achieved using an alkali-fluoride post-deposition treatment; however, its full impact and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
106
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 62 publications
10
106
0
Order By: Relevance
“…This observation indicates that successful alkali PDTs which lead to an improved open‐circuit voltage also reduce the band bending (or at least its variation) at grain boundaries . This observation confirms several numerical studies that show that increased band bending at grain boundaries reduces solar cell efficiency, particularly by reducing the open‐circuit voltage …”
Section: Effects Of Post‐deposition Treatment With Heavy Alkalissupporting
confidence: 84%
See 1 more Smart Citation
“…This observation indicates that successful alkali PDTs which lead to an improved open‐circuit voltage also reduce the band bending (or at least its variation) at grain boundaries . This observation confirms several numerical studies that show that increased band bending at grain boundaries reduces solar cell efficiency, particularly by reducing the open‐circuit voltage …”
Section: Effects Of Post‐deposition Treatment With Heavy Alkalissupporting
confidence: 84%
“…In fact, for KF‐treated Cu(In,Ga)Se 2 , a reduced variation of band bending at grain boundaries was previously also observed, and it was shown by numerical simulations that smaller downward band bending at grain boundaries leads to higher open‐circuit voltage . This observation indicates that successful alkali PDTs which lead to an improved open‐circuit voltage also reduce the band bending (or at least its variation) at grain boundaries . This observation confirms several numerical studies that show that increased band bending at grain boundaries reduces solar cell efficiency, particularly by reducing the open‐circuit voltage …”
Section: Effects Of Post‐deposition Treatment With Heavy Alkalissupporting
confidence: 83%
“…In that respect, scanning probe techniques are ideal tools since they allow us to probe the electronic properties of semiconductors on the nanometer scale. In particular, Kelvin probe force microscopy (KPFM) was used frequently to study band bending at the grain boundaries [21][22][23]. Moreover, the effect of CPE treatment was also investigated on Cu-poor CIGSe with KPFM and it was shown that the band bending at the grain boundaries after CPE treatment was reduced [24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, at the grain boundaries in the surface region, the enhanced Na and K passivate the charged defects to form better contact potential differences (Figure b) . Nicoara et al.…”
mentioning
confidence: 98%
“…Nicoara et al. suggested that charged defects remained at the grain boundaries even after an alkali PDT and the degree of successful passivation of these defects is a key factor for an efficiency improvement . Therefore, under HLS treatment on CsF‐treated CIGS solar cells, the donor defect at grain boundaries might have been successfully passivated by alkali metals (Na and K) migration.…”
mentioning
confidence: 99%